Developing domains to assess understanding regarding sexually transmitted infections among sexually transmitted infection clinic attendees: A qualitative study - Bansari L Chawada; Jayesh K Kosambiya; Vipul P Chaudhari (Wolters Kluwer Medknow Publications, 2017)
Objective: To develop and validate domains to assess attendee's gain at sexually transmitted infection (STI) clinic and their understanding after utilizing services at STI Clinic. Methods: Study was done in two phases. In-depth interviews were conducted to explore attendee's perception. Domains generated through the first phase were validated by conducting another 50 structured interviews. Results: Major domains developed were perceptions on STI, the source of information, treatment seeking behavior, understanding of treatment, laboratory test, and follow-up. Friends and counselor played an important role as the source of right information, while elder family female played a role in delayed seeking care. Conclusion: Developed domains can be used to assess STI clinic attendee's perspective on STI. Poor understanding of STI care component especially prevention, partner treatment, and referral was noted after the clinic visit.